A functional misexpression screen uncovers a role for enabled in progressive neurodegeneration - Rezával, C; Berni, J; Gorostiza, E; Werbajh, S; Fagilde, M; Fernández, M; Beckwith, E; Aranovich, E; Sabio Y García, C; Ceriani, M (Public Library of Science, 2008)
Drosophila is a well-established model to study the molecular basis of neurodegenerative diseases. We carried out a misexpression screen to identify genes involved in neurodegeneration examining locomotor behavior in young and aged flies. We hypothesized that a progressive loss of rhythmic activity could reveal novel genes involved in neurodegenerative mechanisms. One of the interesting candidates showing progressive arrhythmicity has reduced enabled (ena) levels. ena down-regulation gave rise to progressive vacuolization in specific regions of the adult brain. Abnormal staining of pre-synaptic markers such as cystein string protein (CSP) suggest that axonal transport could underlie the neurodegeneration observed in the mutant. Reduced ena levels correlated with increased apoptosis, which could be rescued in the presence of p35, a general Caspase inhibitor. Thus, this mutant recapitulates two important features of human neurodegenerative diseases, i.e., vulnerability of certain neuronal populations and progressive degeneration, offering a unique scenario in which to unravel the specific mechanisms in an easily tractable organism.